PENINGKATAN KEMAMPUAN MEMAHAMI MATERI PEMBELAJARAN BAHASA INDONESIA MELALUI MODEL PENGATUR AWAL - Sri Indrawati (Konstruktivisme : Jurnal Pendidikan dan Pembelajaran, 2014)
This research was intended to increase the ability of Year II students of SLTPN 17 Palembang to comprehend Indonesian learning material through advance organizer. The method used was a three-cycle classroom action research with 4 phases-”planning, implementation, observation, and reflection. The subjects were Class II-9. The results show that the use of advance organizer in the form of text presentation and semantic mapping could increase the ability of the students to comprehend Indonesian learning material.